The spherical harmonic representation of the gravitational field quantities generated by the ice density contrast - TENZER, Robert; ABDALLA, Ahmed; VAJDA, Peter; HAMAYUN, K. (Contributions to Geophysics and Geodesy, 2010)
We derive the expressions for computing the ice density contrast strippingcorrections to the topography corrected gravity field quantities by means of the sphericalharmonics. The expressions in the spectral representation utilize two types of the sphericalfunctions, namely the spherical height functions and the newly introduced lower-boundice functions. The spherical height functions describe the global geometry of the uppertopographic bound. The spherical lower-bound ice functions combined with the sphericalheight functions describe the global thickness of the continental ice sheet. The newlyderived formulas are utilized in the forward modelling of the gravitational field quantitiesgenerated by the ice density contrast. The 30×30 arc-sec global elevation data fromGTOPO30 are used to generate the global elevation model (GEM) coefficients. Thespatially averaged global elevation data from GTOPO30 and the 2×2 arc-deg ice-thicknessdata from the CRUST 2.0 global crustal model are used to generate the global lower-boundice model (GIM) coefficients. The mean value of the ice density contrast 1753 kg/m3 (i.e.,difference of the reference constant density of the continental upper crust 2670 kg/m3andthe density of glacial ice 917 kg/m3) is adopted. The numerical examples are given forthe gravitational potential and attraction generated by the ice density contrast computedglobally with a low-degree spectral resolution complete to degree and order 90 of the GEMand GIM coefficients.